Keragaman Genetik pada Kukang (Nycticebus coucang) Berdasarkan pada gen 12S rRNA Mitokondria - Wirdateti, Wirdateti; Okayama, Toshinao; Kurniati, Hellen (Perhimpunan Biologi Indonesia, 2001)
ABSTRACTGenetic Diversity of Slow loris (Nycticebus coucang) based on Mitochondrial 12S rRNA gene. The research on genetic diversity of slow loris Nycticebus coucang (kukang) was carried out. The samples are 12 individuals from three locations (Sumedang and Jember in Java, and Lampung in Sumatera). Total DNA was extracted from blood and tissue. The mitochondrial 12S rRNA nucleotide sequences were determined to investigate genetic diversity of this species. This region was amplified by using L1091 and H 1478 primers by PCR. As a result of the analysis for 386 bp nucleotide sequence, five haplotypes were found, two from Java and three from Sumatra, respectively.Key words : Slow lories, Nycticebus coucang, genetic diversity, 12S rRNA mtDNA